Ulcer healing activity of Mumijo aqueous extract against acetic acid induced gastric ulcer in rats - Nader Shahrokhi; Zakieh Keshavarzi; Mohammad Khaksari (Wolters Kluwer Medknow Publications, 2015)
Objective: Gastric ulcer is an important clinical problem, chiefly due to extensive use of some drugs. The aim was to assess the activity of Mumijo extract (which is used in traditional medicine) against acetic acid induced gastric ulcer in rats. Materials and Methods: The aqueous extract of Mumijo was prepared. Animals were randomly (n = 10) divided into four groups: Control, sham-operated group (received 0.2 ml of acetic acid to induce gastric ulcer), Mumijo (100 mg/kg/daily) were given for 4 days postacetic acid administration, and ranitidine group (20 mg/kg). The assessed parameters were pH and pepsin levels (by Anson method) of gastric contents and gastric histopathology. Ranitidine was used as reference anti-ulcer drug. Results: The extract (100 mg/kg/daily, p.o.) inhibited acid acetic-induced gastric ulceration by elevating its pH versus sham group (P < 0.01) and decreasing the pepsin levels compared to standard drug, ranitidine (P < 0.05). The histopathology data showed that the treatment with Mumijo extract had a significant protection against all mucosal damages. Conclusion: Mumijo extract has potent antiulcer activity. Its anti-ulcer property probably acts via a reduction in gastric acid secretion and pepsin levels. The obtained results support the use of this herbal material in folk medicine.